2021
DOI: 10.18632/aging.202931
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological improvements in speech-in-noise task after short-term choir training in older adults

Abstract: Perceiving speech in noise (SIN) is important for health and well-being and decreases with age. Musicians show improved speech-in-noise abilities and reduced age-related auditory decline, yet it is unclear whether short term music engagement has similar effects. In this randomized control trial we used a pre-post design to investigate whether a 12-week music intervention in adults aged 50-65 without prior music training and with subjective hearing loss improves well-being, speech-in-noise abilities, and audito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 129 publications
0
25
0
Order By: Relevance
“…Nonetheless, these benefits were also often limited to some of the included measures (n = 8 out of 12, 66.67%). For instance, Hennessy et al (2021) found significant effects for adults' N1 amplitude during passive listening to speech-in-noise, but not for the active speech-innoise task (participants were asked to press a button when they could hear a target syllable).…”
Section: Linguistic Processingmentioning
confidence: 96%
See 3 more Smart Citations
“…Nonetheless, these benefits were also often limited to some of the included measures (n = 8 out of 12, 66.67%). For instance, Hennessy et al (2021) found significant effects for adults' N1 amplitude during passive listening to speech-in-noise, but not for the active speech-innoise task (participants were asked to press a button when they could hear a target syllable).…”
Section: Linguistic Processingmentioning
confidence: 96%
“…Language is one of the far transfer domains most extensively examined in the music training literature. Many studies examine transfer to linguistic abilities including phonological awareness (e.g., Vidal et al, 2020), reading (e.g., Carioti et al, 2019), speechin-noise perception (e.g., Hennessy et al, 2021), speech-in-quiet perception (e.g., Tierney et al, 2015), or prosody perception (e.g., Moreno et al, 2009). Although results from individual studies vary (e.g., Boebinger et al, 2015;Mehr et al, 2013), the mechanisms underlying associations between music and linguistic processing have been discussed.…”
Section: Neurobehavioral Effects Of Music Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…Two more recent studies have confirmed a speech‐in‐noise benefit in older adults as a result of both piano lessons 67 and choir participation 68 . Worschech et al.…”
Section: Musical Training and Hearing Abilitiesmentioning
confidence: 94%